Prediction of Response of Existing Building Piles to Adjacent Deep Excavation in Soft Clay - Yao-Ying Liang; Nian-Wu Liu; Feng Yu; Xiao-Nan Gong; Yi-Tian Chen (Advances in Civil Engineering)
This study investigates building settlements near excavations in soft clay. A simplified theoretical method is proposed to predict the additional settlements and axial forces of excavation-adjacent existing building floating piles in soft clay. The soil displacement is simplified as a line or broken line along the depth direction, depending on the distance from the excavation. A hyperbolic model is applied to calculate the skin friction and tip resistance induced by the vertical soil displacement. The parameters of the hyperbolic model are corrected to fit data from in-service piles. Based on the load-transfer curve method, the additional settlements and axial forces are determined. The measured data of 17 floating piles from two excavation cases in Hangzhou, China, show good agreement with the calculated values. The results show that the position of the neutral point of the loaded pile varies with the soil settlement. Because of the upper structure, the theoretical settlements for piles near the excavation are larger than those obtained from the measured values; for distant piles, this relationship is reversed. The proposed prediction methodology is expected to guide the design of practical excavations.